Simple, selective, and sensitive measurement of urea in body fluids of mammals by reversed-phase ultra-fast liquid chromatography - M. Czauderna; J. Kowalczyk (Czech Journal of Animal Science, 2012)
Ultra-fast liquid chromatography with a photodiode array detector for simple and rapid determination of urea in body fluids of farm animals is described. Blood plasma, milk, and urine samples are treated with trichloroacetic acid and then centrifuged. Supernatants are derivatized at room temperature using p-dimethylaminobenzaldehyde. Samples are separated using a ternary gradient of methanol in buffer and water. Derivatized urea in standards and biological samples is analyzed using a Phenomenex C18-column (Synergi 2.5 µm, Hydro-RP, 100Å, 100 × 2 mm). The photodiode detector is set to 370 and/or 254 nm for detection. Temperature is maintained at 27°C by a column heater. Clear separation of derivatized urea from the endogenous species present in assayed biological samples was achieved in less than 6 min. The urea adduct peak eluted at 4.36 ± 0.05 min. Average recoveries of the urea standards added to assayed biological materials were satisfactory (i.e. 100.2 ± 4.1%). Our chromatographic method with photodiode detection at 370 nm and at 254 nm, in particular, offers low detection (LD) and quantification limits (LQ) (370nmLD = 0.47 ng, 254nmLD = 0.027 ng and 370nmLQ = 1.41 ng, 254nmLQ = 0.080 ng, respectively). Our liquid chromato-graphy based on detection at 370 nm is the most versatile analytical tool that assures sensitive, accurate, and precise analysis of urea in urine, milk, and plasma samples, and selected diets for mammals. The presented chromatographic procedure is especially suitable for preparation of reference sample sets, very accurate and precise research purposes or rapid clinical diagnostic with smaller sample sets. Urea in urine can be also determined using our liquid chromatography with detection at 254 nm. Detection of urine urea at 254 nm is more sensitive and precise compared with monitoring at 370 nm. Our chromatographic method based on photodiode detection at 370 nm and especially at 254 nm is suitable for the non-invasive analysis of urea in only urine of humans and animals.